The culture in fabrication: the 21st century makespace as a flexible, open source tool to inspire a maker community - Bozzonetti, Claudia Lisa (My University, 2017)
The world is standing on the cusp of a third industrial revolution that will see an explosion of creativity, knowledge creation and innovation. South Africa is at the forefront of a different revolution, one that is concerned with the access to knowledge and education. While these revolutions are somewhat different, they fight for the same ideal; that is a world where information and education are available to all, such that people are inspired to innovate, create and empower themselves through the development and use of new knowledge. These revolutions will be facilitated by a number of factors, but what is architecture’s role? This research report discusses a makerspace as an architectural response to the coming knowledge revolution and what this typology means in the context of Johannesburg, South Africa. The author makes reference to the theoretical understanding of maker culture as the celebration of creativity and innovation and that a makerspace facilitates access to the tools and space required so that anyone can make. The intent of this research report is to create an architectural intervention based on extensive research of related theories, careful analysis of the context and various precedent studies. The key issue is determining how the typology affects and is affected by the context. The author utilises the context of Newtown, Johannesburg for the intervention due to its history as a primarily industrial area that grew into a cultural hub of the city. In a World where knowledge has become a privatised commodity, this research report explores how architecture, specifically in the form of a makerspace, can democratise access to information, empower the individual and the community, and boost a stagnant local economy through the encouragement of entrepreneurship.
Thesis is submitted in partial fulfilment for the degree of Master of Architecture to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2017
Keywords: City planning--South Africa--Johannesburg; Markets--South Africa--Johannesburg--Design and construction.